Sarawak Indigenous Music, Unity and Belonging: A Thematic Analysis - Nur Afiqah, Mohamad Sa’id; Chee, Bong; Patrose, Abell Musi; Nur Fatin Liyana, Ghazali; Noor Athirah, Zaini; Collin, Jerome (Asian Scholars Network (002903215-H), 2021)
Numerous studies have shown that indigenous popular music promotes a sense of unity and belonging among people. The study presented in this article extends this line of inquiry by examining visions of unity and belonging among contemporary Sarawakians shaped by their exposure to popular Iban songs. Semi-structured interviews were conducted with 13 participants from the southern, central and northern regions of Sarawak to capture their views on the famous Iban pop song Biar Bekikis Bulu Betis and how it helped construct their sense of unity and belonging. The findings revealed several themes that emerged from the interviews: 1) A fun, familiar, and imperative song for events and festivals, 2) A dancey, catchy, and sing-along song for the people, 3) A song that transcends ethnicity and fosters unity and (4) A song of meaningful lyrics andiconic rhythm. The results also show that the Iban pop song promotes a sense of unity and belonging among Sarawakians. The study has implications for future research as it draws attention to the need to consider the role of indigenous popular music of Malaysia in creating a sense of belonging among the people in this multilingual, multiethnic and multicultural country.